Digital Identity Rights: A Comparative Analysis of Denmark’s and India’s Approaches to Deepfakes (Maharaja Surajmal Institute Law Journal, 2026)
The proliferation of generative artificial intelligence has enabled sophis ticated deepfake technology, posing unprecedented challenges to digi tal identity protection and personal autonomy. This comparative legal  analysis examines Denmark’s 2025 copyright reforms, introducing bio metric likeness protection, against India’s fragmented legal framework  for addressing deepfake-related digital impersonation. Through doc trinal legal research and comparative methodology, this study analyzes  Denmark’s innovative Sections 73a and 65a of the Copyright Act, which  extend intellectual property rights to protect facial features, voice, and  physical characteristics from unauthorized digital imitation. The research  reveals significant gaps in India’s current legal landscape, where privacy  rights, defamation laws, and information technology provisions provide  only piecemeal protection against AI-generated identity theft. Denmark’s  consent-based model, offering post-mortem protection for 50 years and  establishing precise takedown mechanisms, presents a robust framework  that balances individual rights with technological innovation. The find ings demonstrate that India’s adoption of similar copyright-based person ality rights could substantially enhance digital identity protection while  maintaining compatibility with global regulatory standards. The study  offers policy-relevant insights for jurisdictions grappling with AI, intel lectual property, and human dignity.
Keywords: Deepfakes; Digital Identity Rights; Copyright Law; Biometric Likeness; Protection; Comparative Legal Analysis